(untitled) (Revista Contexto & Educação, 2022)
This article aims to analyze the concepts of language, in speech and in practice, of a teacher in the 2nd year of elementary school. The data presented here are an excerpt of a survey carried out in the period 2017 and 2018. From this excerpt, the guiding questions emerged: what are the impacts of the concepts of language in the teaching and learning relationship, with regard to children’s literacy? How does the teacher’s discourse reveal her focus on literacy and how is this reflected in her practice? As the subject of this research, we have the literacy teacher of the Municipal Public School of Education of São Luís, Maranhão, with whom the interview was used as a data generation instrument, as well as participant observation. The studies are based on Bakhtin/Volochinov (2014), Gontijo (2005, 2014), Kleiman (2013), Coracini (1995), Geraldi (2014), Smith (1989, 19999), Jolibert (1994) among others. As a result, we conclude that the formation of readers is directly related to what literacy teachers need to know about the act of reading to teach this cultural object.